FACILITIES AND INFRASTRUCTURE MANAGEMENT IN SERVICE IMPLEMENTATION GUIDANCE AND COUNSELING IN INDONESIAN SCHOOLS - Suhartati Wahyu; Neviyarni Neviyarni; Firman Firman; Muhammad Asyraf Bin Che Amat (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2023)
Facilities and infrastructure function as a support for the implementation of learning and guidance and counseling services in schools. Currently, guidance and counseling facilities and infrastructure in Indonesian schools are not utilized effectively and efficiently so that the implementation of guidance and counseling services is still not successful, in other words it has not achieved the expected goals. Guidance and counseling facilities and infrastructure in schools are not fully supported, thus making it difficult for guidance and counseling personnel to work together in the implementation of guidance and counseling services. Therefore, there is a need for full utilization by guidance and counseling personnel of the available facilities and infrastructure. The purpose of this research is to find out the management of counseling facilities and infrastructure in order to create conducive, comfortable and stable counseling services. This research is a Qualitative Research with the method of literature review (literature review). The results of the study show that the success of counseling services in schools is supported by adequate facilities and infrastructure that are utilized effectively and efficiently. For this reason, the profile of these facilities and infrastructure must be utilized as well as possible.